2019
DOI: 10.3390/en12132533
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Photovoltaic Farms on the Environment in the Romanian Plain

Abstract: Under the European Union (EU) energy efficiency targets that Romania has assumed, increasing the share of solar energy has been one of the main points to be considered. The most important solar energy resources are found in the lowlands and low hills in southern and south-eastern parts of the country. The current paper is focused on the Romanian Plain, which has the best environmental conditions to support the development of photovoltaic (PV) farms. One hundred and ten PV farms have been identified and mapped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 27 publications
0
21
0
5
Order By: Relevance
“…Indirectly, solarland also competes with other land uses such as forest, grass-and scrubland. This structure is based on observed tendencies for solar siting in Europe, India, Japan and South-Korea (see Table S2 in SM), showing that mainly arable land is used for current USSE projects, and supported by academic literature 17,33,34,57,58 and solar industry reports 59,60 . Also, the optimal microclimate for solar energy production (based on insolation, air temperature, wind speed and humidity) is found over land that is currently used as cropland 61 , supporting the assumption that future investors will have a slight preference for cropland (in use or fallow) for the allocation of solar energy projects, among other factors such as flatness and connectivity in terms of roads and electricity grids 22 .…”
Section: Methodsmentioning
confidence: 69%
“…Indirectly, solarland also competes with other land uses such as forest, grass-and scrubland. This structure is based on observed tendencies for solar siting in Europe, India, Japan and South-Korea (see Table S2 in SM), showing that mainly arable land is used for current USSE projects, and supported by academic literature 17,33,34,57,58 and solar industry reports 59,60 . Also, the optimal microclimate for solar energy production (based on insolation, air temperature, wind speed and humidity) is found over land that is currently used as cropland 61 , supporting the assumption that future investors will have a slight preference for cropland (in use or fallow) for the allocation of solar energy projects, among other factors such as flatness and connectivity in terms of roads and electricity grids 22 .…”
Section: Methodsmentioning
confidence: 69%
“…Though our study outcomes revealed that the study area have great potential for solar energy technologies, it is important to consider some drawbacks of such technology, such as negative direct and indirect impacts on natural resources i.e., water utilization and consumption, biodiversity, topsoil and dust, social wellbeing and air quality, transmission passages, and land use land cover alteration [26,27]. Such drawbacks can be overcome by proper policies and strategies that will reduce the negative effects on the ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…Such drawbacks can be overcome by proper policies and strategies that will reduce the negative effects on the ecosystem. However, in all aspects solar energy provides a practical solution for energy scarcity, especially in rural sites [27]. The flexibility of land tenure in South Sudan will promote the adaptation of solar technology at local and national levels, thus will create a friendly investment situation and will eventually assist the developmental activity and reduce poverty in the country.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solar power can be used to generate electricity wherever there is sunshine. Therefore, in the context of the growing global energy demand and increasing concerns relating to resources, environment and climate, governments worldwide have developed a range of policies and incentive mechanisms to promote the development and roll-out of renewable generation technologies for solar and wind energy sources [5]. Solar thermal power generation technology is a relatively mature technology which mainly uses the solar concentrating system to convert the solar energy to a high temperature steam and then drives the generators to generate electricity [6].…”
Section: Introductionmentioning
confidence: 99%